Upaya Meningkatkan Perilaku Disiplin Anak Usia Dini Melalui Parenting di TK Kuwaisyah - Ririn Suryani; Juli Julaiha; Annisa Pahira Nst; Rahmayeni Simanjuntak; Rahma Humairah Nst; Novia Saputri; Rini Lestari Siregar; Asriyani Pasaribu; Nuriyati Nuriyati; Yuliana Andini; Mir-atun Shofiah; Sindi Fauziah (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
This research aims to improve the disciplined behavior of children aged 4-5 years through parenting at Kuwaisyah Kindergarten, Delitua Village, Kec. West Delitua, Kab. Deli Serdang, North Sumatra. The subjects in this study were young children 4-5 years old, namely group A in Kuwaisyah Kindergarten, Delitua Village, Kec. West Delitua, Kab. Deli Serdang, North Sumatra. The method used is a qualitative method with the aim of obtaining in-depth information through parenting activities. Informants are parents who have children and who provide care. The informants were divided into two parts, namely, only one parent who worked or both parents of the child worked. Furthermore, in collecting data using observations, interviews, observations, notes, and documentation (photos). The results of this study indicate that parenting activities can be used as an alternative in improving children's discipline. Keywords:implementation, parenting, disciplined behavior of children aged 4-5 years